- anonymous

Find the solution to 7+8x+-1, 10+h/3=1, m/6+5=26, and -5x-2=13.
Please help.

- jamiebookeater

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

@mthompson440
Please help me

- anonymous

Do you know how to solve for X?

- anonymous

kinda

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

Alright, I might not be able to help you that long because I am leaving soon. But I will try to help as much as I can.

- anonymous

thats ok

- anonymous

sorry, will help you later.

- LynFran

is there a typo with the first problem..?? 7+8x+-1 ??

- anonymous

no its really looks like -1=7+8x

- LynFran

thats a better view...anyways...
we need to solve for x
so we can take 7 frm both sides of the equation
we get -1-7=7-7+8x
simplify we get -1-7=8x
wats -1-7 equals to?

- anonymous

-8

- LynFran

good so -8=8x

- LynFran

we now divide both sides by 8 to solve for x

- LynFran

whats did u get for x?

- anonymous

-1?

- LynFran

correct

- anonymous

I kept on getting -8

- LynFran

-8/8=-1

- LynFran

-8=8x
-8/8=8x/8
-1=x

- anonymous

i get it

- LynFran

ok

- anonymous

how would you do 10+h/3=1

- LynFran

first subtract 10 frm both sides of the equation
so 10-10+h/3=1-10
simplify we get..?

- anonymous

0+h/3=-9?

- LynFran

yes h/3=-9

- LynFran

now we multiply both sides of the equation by b ...that way we can get h alone on the left side of the equation

- LynFran

by 3"

- LynFran

multiply both sides of the equation by 3

- anonymous

-9 times 3 equals -27

- LynFran

yes thats what h= to

- anonymous

-27?

- LynFran

yep

- LynFran

the next equation is done the same way like the previous 1 above
m/6+5=26
whats the first step??

- anonymous

subtract 5 from each side

- LynFran

correct then what??

- anonymous

multiply 6 to each side

- anonymous

I got 126

- LynFran

me too

- anonymous

what about the next equation? the subtraction sign got me

- LynFran

-5x-2=13
we can add 2 to both sides of the equation
reason y... -2+2=0

- LynFran

so we have -5x=13+2
whats next??

- anonymous

13+2 equals 15?

- LynFran

yes -5x=15 now how can we get the x term alone ...since -5 is being multiple to x giving -5x

- LynFran

whats the opposite of multiplication?

- anonymous

division

- LynFran

yes we divide both sides of the equation by.... ??

- anonymous

5?

- LynFran

shd be -5

- LynFran

if we divide by 5 then we have -x=15/5

- anonymous

so x equals -3

- LynFran

correct

- anonymous

Could you help me with -1=4+x/3?

- LynFran

what the first step...do u know..?

- anonymous

subtract 4 from each side

- LynFran

correct

- anonymous

so, x/3=-5

- LynFran

yes now whats the next step?

- anonymous

multiply 3 to each side

- LynFran

correct

- anonymous

so, x=-15?

- LynFran

yep

- anonymous

Thank you very much for helping me!

- LynFran

welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.